WAKAF UANG UNTUK PENGEMBANGAN OPERASIONAL KEGIATAN MASJID - Nurul Huda; Hulmansyah Hulmansyah; Zulihar Zulihar (JURNAL PENGABDIAN AL-IKHLAS UNIVERSITAS ISLAM KALIMANTAN MUHAMMAD ARSYAD AL BANJARY, 2019)
This low waqf fund was due to the lack of education about money waqf. The general public in Indonesia is more familiar with the term waqf with immovable property such as mosques or land and the allocation of waqf is mostly used for the purposes of worship, burial, and education. This training aims to better socialize money waqf to help develop operational activities of mosques. The method is used in the form of training and mentoring for mosque administrators. The results of the Pre and post-test training test have a significant effect on participants' knowledge regarding money waqf.